Avaliação do ácido kójico no processo de vinificação - Emer, Cassandro Davi (2022)
The search for alternatives to sulfur dioxide (SO2) in its most different uses within winemaking instigates the evaluation of new compounds. Kojic acid has several applications within the food industry and has recently been used in the cosmetic industry, mainly for its capacity of enzyme inhibition. Its presence in the diet of oriental cultures goes back centuries, given its existence in various fermented foods as a metabolic by-product of the fermentative process. This work evaluates the effect of kojic acid in the winemaking process as an alternative to pre-fermentative sulfur dioxide, observing its consequences in the oenological and sensorial parameters of the products, since sulfur dioxide has an important role, not only as an antioxidant and antimicrobial agent during the fermentative process, but in the aromatic profile of the final wine. The experiment was carried out using a fully randomized design, in triplicates, with one treatment of potassium metabisulfite (100 mg L−1), two with different concentrations of kojic acid (100 mg L−1 and 200 mg L−1) and a control. The fermentation kinetics showed an impact of SO2 on the lag phase, not differing among the other treatments. A distinction was observed between the trials with regard to the concentration of malic acid, both after the end of the alcoholic fermentation, and during, suggesting the metabolization of malic acid at the beginning of the fermentative process in the treatments free of sulfur dioxide, the hypothesis being supported by the increase in lactic acid content. After a period of 6 months in conditions favorable to oxidative processes, the main oenological attributes of the wines were evaluated, observing differentiation in the levels of higher alcohols and total sulfur dioxide between the treatment with SO2 and the others. Also, a higher value for total aldehydes was found compared to the other treatments, suggesting that the presence of the SO2 in the pre-fermentative and fermentative stages may have played a role in preserving these compounds in sulfonated forms, releasing them in the post-fermentative stage. Sensory analysis suggests the ability of kojic acid to inhibit enzymatic oxidation by preserving the visual quality of the wines, as well as providing sensory profiles close to the sulfur dioxide treatment, without showing notes of dried fruits, as observed in the control treatment. Furthermore, the treatment with 100 mg L−1 of kojic acid achieved distinction in the descriptors Taste Appreciation, Olfactory Intensity and Olfactory Appreciation. Kojic acid showed potential as an alternative to pre-fermentative SO2, opening up a range of possibilities for future studies.